(untitled) (Journal of Asian Development Studies, 2025)
Computer-generated images (CGI) influencers represent a new force in digital marketing, yet their adoption in conservative markets remains under-researched. This study examines the influence of influencer personalisation on building consumer attachment, the impact of attachment on purchase intention, and the mediating role of brand credibility. We sampled 150-200 social media users who were exposed to CGI influencers in conservative societies, i.e., in the Middle East and South Asia. Findings indicate that personalisation has a significant positive impact on attachment, and this effect is, in turn, mediated by personalisation and purchase intention. In addition, brand credibility amplifies this mediated effect, underscoring the importance of trust in a culturally sensitive context. The results suggest the use of CGI-driven campaigns, personalised with cultural authenticity, to influence consumer behaviour in conservative markets.